(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the unique features of the works of poets Zebo Mirzo, Khosiyat Rustamova, Guljamol Askarova, who skillfully swing a pen in modern Uzbek poetry, will be highlighted. Also, lines are interpreted as the image of the soul in the works created by these artists.